The Role of Instagram Influencers in Enhancing Yogyakarta’s Appeal to Millennial and Gen Z Travelers - Fahrais Zahrudy; Fitria Maulida; Fiko Rahardito Baskoro; Dimas Bayu Arya Putra (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2025)
Background: Instagram influencer marketing is increasingly becoming a determining factor in the decision-making of Millennials and Gen Z regarding visits to tourism destinations. Although source credibility (attractiveness, trustworthiness, and expertise) has been widely studied, little is known about its direct influence on behavioral intention when mediated by affective mechanisms. Purpose: This study examines how parasocial interaction (PSI) mediates the relationship between source credibility and travel intention, i.e., the tendency to visit Yogyakarta. In this context, PSI refers to the emotional connection that allows followers to feel attached to influencers. Method: Data were collected via an online survey distributed via Google Forms to Indonesian Instagram users between January and March 2025. Purposive sampling was employed to obtain 213 responses from users who follow travel influencers. The data collected were analyzed using PLS-SEM. Findings: The results show that attractiveness, trustworthiness, and expertise have no direct impact on travel intention. However, all these credibility dimensions show a strong positive correlation with PSI, which predicts travel intention. Therefore, PSI is identified as a complete mediator in the model. Conclusions: Travel intention is mainly driven by emotional connection rather than by influencer traits alone. The appraisal mechanism mediates the process from perception to action. Research Implication: It is recommended that tourism marketers adopt PSI-based strategies by recognizing actors who can build substantive, affective relations with the audience.